Separatists, state subjectivity, and fundamental ontological (in)security in international relations. (September 2022) - Grzybowski, Janis
Ontological security studies (OSS) in International Relations (IR) emphasize the role of identity, anxiety, and a sense of self in world politics. Yet suggesting that states act in certain ways because of 'who they are' also assumes that they are in fact states. In this article, I problematize the presupposition of state subjects in the context of separatist conflicts in which claims to statehood compete and overlap. Where unrecognized de facto states are pitted against their unyielding parent states, the two threaten each other's very state personhood, thereby presenting a more radical challenge to their existence than traditional 'physical' and 'ontological' security threats. Separatist conflicts thus reveal a widely overlooked dimension of fundamental ontological security, provided by the constitution and recognition of states as such. Moreover, because of the exclusiveness of state subjects in the modern international order, any third parties attempting to resolve such conflicts inevitably face a meta-security dilemma whereby reassuring one side by confirming its claim to statehood simultaneously renders the other side radically insecure. Thus, rather than regarding particular state subjects as merely the starting point of quests for ontological security in international relations, they should also be understood as already their result.